A Mixed-Methods Approach to Understanding the Palliative Needs of Parkinson's Patients. (August 2020) - Prizer, Lindsay P.; Gay, Jennifer L.; Wilson, Mark G.; Emerson, Kerstin G.; Glass, Anne P.; Miyasaki, Janis M.; Perkins, Molly M.
Parkinson's disease (PD) is the second-most common age-related neurodegenerative disorder. Despite recommendations for a palliative approach, little is known about what palliative needs are unmet by standard care. This study aims to (a) identify palliative needs of PD patients, (b) determine the relationship between palliative needs and health-related quality of life (HRQoL), and (c) probe into factors affecting HRQoL. PD patients and neurologists were recruited for a survey on palliative need; a subset of patients was interviewed. Significant differences between physicians and patients were found in Physical, Psychological, Social, Financial, and Spiritual domains. Physical and Psychological needs predicted HRQoL. Primary themes across interviews included (a) lack of healthcare education and (b) need for care coordination. Secondary themes included (a) the importance of support groups, (b) the role of spirituality/religion, and (c) the narrow perceived role of the neurologist. Findings highlight the importance of coordinated individualized care.